The flipside of hope discourse: avoiding accountability and assigning responsibility in sustainability transitions - Bergeå, Hanna; Åhlvik, Therese; Hallgren, Lars (Frontiers in Communication, 2025)
Nowadays, environmental scholars and practitioners largely embrace the importance of characterizing environmental communication via messages of hope. Overall, research on hope and communication suggests that strategically designed hope messages can foster pro-environmental attitudes and behaviors. However, such research tends to focus solely on the instrumental aspects of communication. Conversely, research emphasizing the social function of hope considers it a discursive phenomenon that people actively use in interactions to perform different social actions. Accountability, responsibility, and agency are central features of hope discourse, and it is important that they are addressed in environmental communication and management to move from good intentions and high ambitions to action. In this paper, we examine how these issues are managed in inspirational meetings that promote the transition to a circular economy, one that is largely regarded as a promising strategy for solving contemporary environmental issues. We adopt the methodology of discursive psychology and analyze how the hope discourse that dominates these meetings is constructed, situated, and oriented toward action. We find that meeting participants use hope discourse to not only downplay problems and challenges but also avoid issues of accountability for claims that can be considered negative or pessimistic. Hope discourse can also be used to assign responsibility to others as well as to renounce it personally, thereby externalizing responsibility and construing hope as a passive act. Furthermore, hope discourse enables participants to portray themselves as active and agentic by claiming responsibility and making commitments to realize a circular economy, while bringing about change. However, such commitments tend to be non-specific, and participants rarely clarify the extent of their responsibility or the actions they encompass. We conclude that hope discourse relates to accountability, responsibility, and agency in ambiguous and variable ways; therefore, environmental scholars and practitioners should critically engage with such a discourse by identifying when it enables the joint exploration of problems and challenges and when it closes down.